Residual water content of excavated soil in EPB tunnelling. (August 2021) - Galli, Mario; Thewes, Markus; Freimann, Sascha; Schröer, Marius
Highlights: Not only the foam water but also the residual water is present in the soil matrix. Water content of excavated soil is a leading parameter for soil conditioning. Range of realistic water contents for different EPB tunnelling situations developed. Foam Penetration Tests can be used to evaluate the residual water content. Abstract: The water content of the excavated soil in EPB (Earth Pressure Balance) tunnel construction controls the amount of conditioning of the excavated material in the excavation chamber. The water content influences crucial performance parameters (conditioning, wear, support pressure, etc.). With regard to foam conditioning, this means that the less water enters the excavation chamber, the drier the soil-foam mixture with constant foam properties. Especially in cohesionless soils below the groundwater level, the amount of free pore water is quite high. The cutting process, the effective pressure state and the use of conditioning agents result in flow processes of pore water and foam, which can lead to the displacement of water from the pore space at the tunnel face. Therefore, only residual moisture is present when the soil enters the excavation chamber. However, how much water enters the excavation chamber is still not determinable and not considered designing soil conditioning for the TBM drive. In this study, the initial water content was linked to an analysis of the residual water content entering the excavation chamber during EPB advance. Foam Penetration tests with different cohesionless soils were performed on the laboratory scale to analyze the residual water content. From the laboratory tests, water contents for the design of soil conditioning concepts can be determined for specific tunnelling situations.